Antispasmodic and Toxicological Effects of Methanol Extract of Chromolaena odorata on Jejunum Muscle in Animal Models - Ukah, Armstrong C.; Tologbonse, Adedayo A.; Onyeukwu, Nkechi J.; Michael, Archibong A.; Mbagwu, Herbert O.C.; Omeluko, Mmaduabuchi N.; Abam, Ejika I.; Tologbonse, Titilayo E.; Attah, Susana A.; Elochukwu, Chukwuemelie G.; Otimanam, Hillary E. (Nigerian Journal of Pharmaceutical and Applied Science Research, 2026)
Background: Chromolaena odorata is widely used in traditional medicine and possesses considerable therapeutic potential for managing conditions such as diabetes, malaria, wounds, gastrointestinal disorders, and inflammation. Its bioactive constituents may provide a basis for novel therapeutic agents. Objectives: This study evaluated the in vitro intrinsic contractility/relaxation effects of orally administered methanol extract of C. odorata on jejunum smooth muscle and assessed its in vivo effects on jejunal histological integrity in rat models. Methods: Acute toxicity was assessed in thirty adult mice (20–30 g) using a modified Lorke’s method. In vitro studies were conducted using jejunum tissues obtained from twenty mature Wistar rats (180–200 g) divided into four groups. Jejunum strips were mounted in an organ bath containing Tyrode’s solution to assess smooth muscle responses. Histological evaluation of harvested jejunum tissues was performed using Mayer’s haematoxylin and eosin staining. Results: The median lethal dose (LD??) was 2738.61 mg/kg, indicating relatively low acute toxicity. The extract produced dose-dependent antispasmodic effects on jejunum smooth muscle, mediated partly through muscarinic receptor inhibition, as evidenced by atropine antagonism. Maximum relaxation (?7.0 ± 0.58 mm; 100% response) was observed at 2 × 10?² mg/mL. Histological findings showed preserved tissue architecture at low doses, with moderate mucosal alterations at higher doses. Conclusion: C. odorata methanol extract exhibits dose-dependent antispasmodic activity mediated mainly via muscarinic receptors. While low doses appear safe, higher doses may compromise mucosal integrity, highlighting the importance of dose optimization and supporting its traditional use in gastrointestinal disorders.